Effect of electrified surface casing on the interference characteristics of stray current generated by deep‐well anode beds. Issue 5 (22nd December 2022) - Cen, Kang; Dai, Minxue; Huang, Xiayu; Han, Zongzhi; Dong, Chunjuan; Li, Renke
Abstract: Currently, the impressed current cathodic protection with deep‐well anode beds has been found that the surface casing was charged. In this study, 13 deep‐well anode beds were selected randomly to investigate whether their surface casings were electrified. Possible causes of the electrification of surface casings are also discussed. A numerical model for simulating the geoelectric field of a representative deep‐well anode bed with an electrified surface casing was established and validated by data from on‐site testing. The difference in the interference characteristics between situations with charged and uncharged casings was also discussed. The results showed that 30.7% of deep‐well anode beds had electrified surface casings. The leading root causes may be that the anode cable had been damaged unexpectedly during the construction process or the electrical resistance between the anodes and the surface casing had been reduced dramatically. The peak potential gradient and comprehensive interference intensity were about 20 times and 3–6 times, respectively, those in situations where the casing was uncharged. A polyvinyl chloride surface casing is, therefore, recommended in deep‐well anode beds. Reliable electrical insulation should be implemented if steel casings are used. Furthermore, regular electrification tests on steel surface casings should be conducted during completion acceptance and daily operation. Abstract : Thirteen deep‐well anode beds were selected randomly to investigate whether their surface casings were electrified. The difference in the interference characteristics between situations with charged and uncharged casings was also discussed. It should be noted that 30.7% of the surface casings were charged. The peak potential gradient and comprehensive interference intensity were about 20 times and 3–6 times, respectively, those in situations where the casing was uncharged.